The Establishment of the Institute of Tax Consulting in the Context of State Regulation - Anastasiya Aleksandrovna Orlova (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2018)
The article is devoted to the establishment of the Institute of tax consulting in Russia. Consider the stages of formation and development of tax consulting in the Russian Federation. The contribution of the professional associations of tax consultants in the development of the tax consulting market. Defined the modern advanced trends in the interaction of the Federal tax service and taxpayers. The author proposes the creation of regulated terms of the functioning of the Institute of tax consulting, contributing to the development of a civilized market of consulting services.